1966
DOI: 10.1002/app.1966.070100402
|View full text |Cite
|
Sign up to set email alerts
|

Proposed mechanism for the curing of epoxy resins with amine‐lewis acid complexes or salts

Abstract: SynopsisThe common assumption in the literature is that amine complexes of Lewis acids (particularly boron trifluoride) cure epoxy resins by virtue of their dissociation to liberate the Lewis acid which then functions as the "true" catalyst. Evidence is presented to indicate that this picture of aminelewis acid complex curing may be incorrect. Another mechanism is proposed which is consistent with ( a ) lack of correlation between adduct stability and reactivity, ( b ) a similarity in reactivity of BF, adducts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

1983
1983
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(22 citation statements)
references
References 9 publications
0
21
0
1
Order By: Relevance
“…Harris and Temin [260] refuted the assumption of thermal dissociation of the complex. Indeed, they observed that BF 3 -amine complexes are thermally stable up to their sublimation temperature.…”
Section: Page 27 Of 163mentioning
confidence: 96%
See 1 more Smart Citation
“…Harris and Temin [260] refuted the assumption of thermal dissociation of the complex. Indeed, they observed that BF 3 -amine complexes are thermally stable up to their sublimation temperature.…”
Section: Page 27 Of 163mentioning
confidence: 96%
“…Due to their higher stability, BF 3 -amine complexes are usually preferred. Several authors demonstrated that the reactivity of such complexes increases with decreasing basicity of the amine [63,260]. For instance, Pascault and coworkers observed that BF 3 -aromatic amine complexes do not show latency (aniline, pKa=4-5).…”
Section: Bf 3 -Lewis Base Complexesmentioning
confidence: 99%
“…The approach utilized in the above calculations is approximate, but it does account for the effect of the moving bubble-resin boundary on the concentration profile and diffusion. 4. If the prepreg is equilibrated with moisture at a relative humidity, (RH)0, then in order to prevent the potential for void growth by diffusion at all times when the temperature during the curing cycle is T(t), the pressure at all points of the prepreg P(t) must satisfy the following inequality: where (RH)0% -the relative humidity to which the prepreg was exposed.…”
Section: Compaction and Resin Flowmentioning
confidence: 99%
“…6 They found similarity in the action of amine-boron triCuring of epoxy resin is by either step-growth refluoride complexes and the corresponding amine actions with curing agents such as amines, tetrafluoroborate salts in epoxy curing. This impolyphenols, or by chain growth reactions with plied that the predominant catalytic species are Lewis acids and bases.…”
Section: Introductionmentioning
confidence: 96%
“…4,5 They concluded that the by the BF 3 complexes are tetrafluoroborate salts. primary step in curing is the reaction between the The fact that the amine boron trifluoride complex anion and the epoxy group, while the oxonium ion and the corresponding fluoroborate salts have might convert slowly into a carbonium ion, and similar reactivity 6 suggests that tetrafluoroborate the crosslinking reaction is initiated by attack of ion is another source for catalyzing the curing rethe carbonium ion on the epoxy ring. In other action.…”
Section: Introductionmentioning
confidence: 97%